Increased Hepatitis E Virus Seroprevalence Correlates with Lower CD4+ Cell Counts in HIV-Infected Persons in Argentina - Debes, José D. (2016)
Hepatitis E virus (HEV) is a single-stranded RNA virus that can cause hepatitis in an epidemic fashion. HEV usually causes asymptomatic or limited acute infections in immunocompetent individuals, whereas in immunosuppressed individuals such as transplant recipients, HEV can cause chronic infections. The risks and outcomes of HEV co-infection in patients infected with human immunodeficiency virus (HIV) are poorly characterized. We used a third generation immunoassay to measure serum IgG antibodies specific for HEV in 204 HIV-infected individuals from Argentina and a control group of 433 HIV-negative individuals. We found 15 of 204 (7.3%, 95%CI 3.74-10.96%) individuals in the HIV-positive group to have positive HEV IgG levels suggestive of previous infection, compared to 19 of 433 (4.4%, 95% CI 2.5-6.3%) individuals in the HIV-negative control group (p = 0.12). Among HIV-positive individuals, those with HEV seropositivity had lower CD4 counts compared to those that were HEV seronegative (average CD4 count of 234 vs 422 mm3, p = 0.01), indicating that patients with lower CD4 counts were more likely to be HEV IgG positive. Moreover, HEV seropositivity in patients with CD4 counts <200 mm3 was 16%, compared to 4.5% in those with CD4 counts >200 mm3 (p = 0.012). We found a positive PCR result for HEV in one individual. Our study found that increased seroprevalence of HEV IgG correlated with lower CD4 counts in HIV-infected patients in Argentina.